1987
DOI: 10.1088/0029-5515/27/12/004
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy balance in T-10

Abstract: The authors report the results of ion temperature measurements in the T-10 tokamak, with allowance for corrections due to the effect of kinetic transport of ions to the energy spectrum of atoms. On the basis of the experimental data they analyse the ion energy balance in the Ohmic heating and ECRH regimes over a broad range of plasma parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Measurements of the time evolution of the 15 MeV proton emission indicated that 0.8 MeV 3 He ions [5] and fast wave heated 3 He minority ions [6] slowed down at roughly the expected rate. On T-10, the time evolution and magnitude of the drop in ion temperature during electron cyclotron heating was consistent with the expected reduction in power flow from the electrons [7]. Although each of these experiments was consistent with classical theory, their accuracy was such that deviations as large as 50%, or more, from theory may have escaped detection.…”
Section: Comparison Of Experimental and Theoretical Fast Ion Slowing-supporting
confidence: 65%
“…Measurements of the time evolution of the 15 MeV proton emission indicated that 0.8 MeV 3 He ions [5] and fast wave heated 3 He minority ions [6] slowed down at roughly the expected rate. On T-10, the time evolution and magnitude of the drop in ion temperature during electron cyclotron heating was consistent with the expected reduction in power flow from the electrons [7]. Although each of these experiments was consistent with classical theory, their accuracy was such that deviations as large as 50%, or more, from theory may have escaped detection.…”
Section: Comparison Of Experimental and Theoretical Fast Ion Slowing-supporting
confidence: 65%
“…A previous transport analysis of neutral beam heated plasma discharges in the Dili tokamak [1] showed that the ion thermal diffusion coefficient Xi not only was non-neoclassical in magnitude but also exhibited a different radial dependence. In the T-10 tokamak [2], Xi f°r various Ohmic and RF heated plasmas was found to be 1.5 to 4 times the neoclassical value. Ion transport was also found to be anomalous in beam heated ASDEX [3] discharges.…”
Section: Introductionmentioning
confidence: 89%
“…The electron temperature profiles Tg Xp (r) were measured by the 2nd harmonic of electron cyclotron emission (ECE), soft X-ray (SXR) spectra and Thomson scattering of laser beams. The ion temperature profiles Tj exp (r) were determined by charge exchange spectra, Doppler broadening of visible carbon lines (on the plasma edge) and absolute measurements of neutron flux (in the plasma core) [19].…”
Section: Simulation Of Ecrh Experiments On T-10mentioning
confidence: 99%